2003
DOI: 10.1016/s1525-0016(03)00041-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cyclic stretch on gene transfer in alveolar epithelial cells

Abstract: Cyclic stretch has been shown to alter cell physiology, cytoskeletal structure, signal transduction, and gene expression in a variety of cell types. To determine the effects of stretch on the gene transfer process, we compared the transfection efficiencies of human A549 cells grown either statically or exposed to 10% cyclic stretch (Delta surface area) at 60 cycles/min (1 Hz) for 24 hours prior to, and/or after transfection with pEGFP-N1 and pCMV-lux-DTS using lipoplex or electroporation. Stretching the cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 58 publications
2
37
1
Order By: Relevance
“…8 As shown in Figure 3a, as little as 30 min of cyclic stretch was also sufficient to decrease the amount of polymeric tubulin as determined by Western blot, but had little to no effect on microfilaments ( Figure 3b). The depolymerization of the microtubules following 30 min of stretch caused a 50% reduction in microtubules that did not recover when the cells were then grown under static conditions for up to 24 h. This suggested that the stretch-induced changes in the microtubule network due to 30 min of cyclic stretch were retained by the cells throughout the course of our experiments.…”
Section: Short Durations Of Cyclic Stretch Cause Depolymerization Of mentioning
confidence: 82%
See 3 more Smart Citations
“…8 As shown in Figure 3a, as little as 30 min of cyclic stretch was also sufficient to decrease the amount of polymeric tubulin as determined by Western blot, but had little to no effect on microfilaments ( Figure 3b). The depolymerization of the microtubules following 30 min of stretch caused a 50% reduction in microtubules that did not recover when the cells were then grown under static conditions for up to 24 h. This suggested that the stretch-induced changes in the microtubule network due to 30 min of cyclic stretch were retained by the cells throughout the course of our experiments.…”
Section: Short Durations Of Cyclic Stretch Cause Depolymerization Of mentioning
confidence: 82%
“…After allowing for attachment for 48-72 h, the cells were stretched using 25 mm BioFlex loading stations with a 10% membrane surface area change at 30 cycles per minute and a 50% duty cycle. These parameters are the same as previously reported, 8 and the 25 mm loading stations ensure an equibiaxial stretch in the radial and circumferential directions over the width of the loading post.…”
Section: Equibiaxial Cyclic Stretchmentioning
confidence: 93%
See 2 more Smart Citations
“…A more physical approach, cyclic cell stretching, has also been employed as a means of increasing in vitro gene delivery efficiency. 6 Future studies will likely exploit embedded polymer matrices in combination with undifferentiated stem cells to initiate and promote tissue growth in vitro for implantation. Such a system would be widely applicable, as the gene embedded into the matrix could be varied in order to alter the stem cell differentiation pathway.…”
mentioning
confidence: 99%